Investigating the design of macromolecular-based inks for two-photon 3D laser printing [data] - Catt, Samantha; Vázquez-Martel, Clara; Blasco, Eva (Universität, 2025)
Two-photon 3D laser printing (2PLP) is one of the most versatile methods for additive manufacturing of micro- to nano-scale objects with arbitrary geometries and fine features. With advancing technological capability and accessibility, the demand for new and versatile inks is increasing, with a trend toward printing functional or responsive structures. One approach for ink design is the use of a macromolecular ink consisting of a ‘pre-polymer’ functionalized with photocrosslinkable groups to enable printability. However, so far the synthesis of pre-polymer inks for 2PLP often relies on an arbitrary choice rather than systematic design. Additionally, current structure–property relationship studies are limited to commercial or small molecule–based inks. Herein, three macromolecular inks with varied compositions, molecular weights, and glass transition temperatures are synthesized and formulated into inks for 2PLP. 3D microstructures are fabricated and characterized in-depth with scanning electron microscopy as well as infrared spectroscopy and nanoindentation to enable the determination of structure–processability–property relationships. Overall, it is clearly demonstrated that the macromolecular design plays a role in the printability and mechanical properties of the obtained materials.